De l’apport de la pensée militaire classique aux études stratégiques modernes - Fortmann, Michel; Gongora, Thierry (Études internationales, 1989)
In this article, the authors try to define the general conceptual framework of classical strategic thought in order to assess its relevance for the development of contemporary Strategic Studies. Our argument brings out the fact that classical strategic scholars tended to conceptualize strategy as the scientific study of conflictual actions between unitary actors, omitting by this very fact to study the sociopolitical dimensions of conflicts, the impact of military technology or the influence of organizational and decisional processes on the conduct of war. Nevertheless, classical strategic thought still offers an invaluable body of literature to understand the evolution of ideas on war, and a possible way of enriching strategic studies through the use of its distinctive comparative historical perspective.